2000
DOI: 10.1046/j.1365-2958.2000.01890.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes affecting selenite toxicity and resistance in Saccharomyces cerevisiae

Abstract: SummaryRecent studies associating dietary selenium with reduced cancer susceptibility have aroused interest in this substance. In the millimolar range, selenite is toxic and slightly mutagenic for yeast. We show that selenite-treated yeast cells tend to arrest as large budded cells and that this arrest is abolished in a rad9 mutant that is significantly sensitive to selenite. Interestingly, a rev3 mutant affected in the errorprone repair pathway is also sensitive to selenite, whereas mutations in the other DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
3
5

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 35 publications
5
69
3
5
Order By: Relevance
“…2(b) for the respective W303 background strains (data not shown). As expected from Pinson et al (2000), the proportion of wild-type viable cells which became can R increased with the duration of selenite treatment, confirming the mutagenicity of selenite under our experimental conditions (Fig. 7a).…”
Section: Selenite Provokes An Increase Of Protein Carbonylationsupporting
confidence: 87%
See 1 more Smart Citation
“…2(b) for the respective W303 background strains (data not shown). As expected from Pinson et al (2000), the proportion of wild-type viable cells which became can R increased with the duration of selenite treatment, confirming the mutagenicity of selenite under our experimental conditions (Fig. 7a).…”
Section: Selenite Provokes An Increase Of Protein Carbonylationsupporting
confidence: 87%
“…In fact, S. cerevisiae, and fungi in general, do not contain selenoproteins and therefore Se is not essential for these organisms (Lu & Holmgren, 2009). High concentrations of Se cause DNA double-strand breaks in exponentially growing S. cerevisiae cells (Letavayová et al, 2008) and RAD9-dependent cell cycle arrest (Pinson et al, 2000). Accordingly, yeast mutants defective in the RAD9-mediated DNA repair pathway or the RAD6/RAD18-mediated DNA damage tolerance pathway are hypersensitive to sodium selenite (Seitomer et al, 2008), pointing to the importance of DNA damage in explaining Se toxicity to yeast cells.…”
mentioning
confidence: 99%
“…Toxicity-The toxicity of selenite in yeast is well documented, although the mechanisms of toxicity are less well understood (24,25). Selenite uptake is the first step in selenium metabolism that ultimately leads to toxicity.…”
Section: Effect Of Phosphate On Selenitementioning
confidence: 99%
“…Although classic studies revealed that SeMet was efficiently incorporated into the Met pathway (7), the toxicity of SeMet has not been examined in yeast. In contrast, the effects of selenite have been studied by several groups spanning several decades (15,(22)(23)(24)(25), underscoring the importance of yeast as a model system for deciphering the mechanisms of selenium toxicity. Indeed, recent data analyzing the role of genes in the RAD9-dependent DNA repair pathway, the RAD6/RAD18 DNA damage tolerance pathway, and the oxidative stress pathway DNA damage tolerance pathway in S. cerevisiae suggest that both selenite and SeMet are likely inducing DNA damage by generating reactive species (19).…”
Section: Semet Incorporation Into Proteins In a Cys3⌬ Null Strain By mentioning
confidence: 99%